Teleworking and Work-Family Reconciliation in the Public Sector: Impact of Gender and Family - Andres Jimenez-Figueroa; Carlos Javier Ossa-Cornejo; Veronica Edith Gomez-Urrutia (RAN, 2024)
Purpose: To analyze Chilean public servants’ perception of working from home and work-family reconciliation.